AB0414 ESSPRI COMPONENTS AND SALIVARY FLOW RATE ARE RELATED TO DAILY ACTIVITY IMPAIRMENT IN PATIENTS WITH PRIMARY SJÖGREN'S SYNDROME. (2nd June 2020) - Mumcu, G.; Abacar, K.; Tatli, İ.; Yenisoy, Y.; Kapusuz, A.; Çakir, E. N.; Türe-Özdemir, F.; Direskeneli, H.; Inanc, N.
Abstract : Background: Sjögren's syndrome (SjS) is a chronic systemic autoimmune disease targets primarily the salivary and lacrimal glands, the severe dryness of the mouth and eyes are common manifestations in patients. Therefore, daily life could be affected by these manifestations in patients with SjS. Objectives: The aim of the study was to assess associations among daily activity impairment and scores of EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI) and major salivary gland ultrasonography (SGUS) in primary SjS. Methods: In this cross-sectional study, 41 patients with primary SjS (F/M:39/2; mean age: 52, 1±10, 5) were included. The mean disease duration was 9.5±6, 6 years in the group. Data were collected by clinical examinations and a questionnaire regarding two patients reported outcome measures (PROMs). Firstly, Work Productivity and Activity Impairment (WPAI) questionnaire assessed paid and unpaid work during the last seven days. Scores of WPAI subgroups as absenteeism, presenteeism, overall work impairment as well as daily activity impairment were calculated by using 6 items. Secondly, dryness, fatigue and pain in ESSPRI scale were evaluated by visual analogue scale (VAS; 0-10 points) in SjS. High scores in both PROMs indicates that disease manifestations affect patient 'life poorly. In addition, structural damage of parotid and submandibular salivary glands were examined by using Milic and Hocevar USG scoring methods. Unstimulated whole salivary flow rate (U-WSFR; as ml/min) were also used to interpret the functional status of major salivary glands. High SGUS score and low U-WSFR reflects that disease activity affects major glands poorly. Results: Daily activity impairment was calculated as 63, 9±31, 1 in patients with primary SjS. High scores in ESSPRI-dryness, ESSPRI-fatigue and ESSPRI-pain were also observed in the group (7, 5±2, 4; 6, 4±2, 8 and 6, 1±3, 1, respectively). Daily activity impairment was correlated with scores of ESSPRI-dryness (r:0, 55 p=0.000), ESSPRI-fatigue (r:0, 38 p=0.014) and ESSPRI-pain (r:0, 56 p=0.000) as well as parenchymal inhomogeneity USG scores of right and left parotid glands (r:0, 49 p=0.032; r:0, 51 p=0.025). U-WSFR (0.20±0.20 ml/min) was moderately correlated with parenchymal inhomogeneity USG scores of major salivary glands (p<0.05). ESSPRI-dryness score was significantly higher in patients with low U-WSFRs (≤ 0.1 ml/min) than the others (87, 5±16, 3 vs 68, 3±25, 1, respectively)(p=0.021). Conclusion: Firstly, subgroup scores of ESSPRI and low U-WSFR associated to daily activity impairment in patients with primary SjS. Secondly, parenchymal inhomogeneity scores of both parotid glands could give an important clue to clinicians for the disease-related damage. Finally, WPAI with 6-item could be thought as an useful tool to understand the effect of the disease manifestations on patients' daily life. Disclosure of Interests: None declared